Linguistic and Cultural Dimensions of Loyalty: A Comparative Study of English and Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores how the concept of loyalty is expressed in English and compares it with its Uzbek equivalent, sadoqat. The study draws on corpus evidence from the British National Corpus, and authentic discourse materials (media texts, political speeches, and literary works), and dictionary sources such as Cambridge and Oxford. To make the analysis more systematic, the expressions of loyalty were grouped into six main area: personal, professional, socio-political, moral, religious, and commercial. The findings show that while loyalty is universally linked with ideas of trust and steadfastness, it takes on different nuances depending on cultural and social context. English makes finer distinctions, using a wide range of words to separate emotional, institutional, and commercial types of loyalty. Uzbek, by contrast, conveys the same value through fewer but semantically richer terms, most of which carry strong emotional and ethical associations. This comparison highlights not only linguistic differences but also the cultural values that shape how loyalty is understood in the two traditions.